Pengabdian Kepada Masyarakat Melalui Ekonomi Kreatif Wedang Jahe Srr...Bukhe Bulang Lintang RT.02 Kota Batam - Delladari Mayefis; Suci Fitriani Sammulia; Ghalib Syukrillah Syahputra; Desy Maniarti Gusmali (Pusat Riset dan Inovasi Nasional, 2021)
Ginger drink is a traditional beverage made from red ginger (Zhingiber officinale Rosc.var.rubrum), which is commonly used as a spice, a warming agent, and a raw material for traditional medicine. Ginger drink is a product that faces increasing competition, especially with the growing number of instant ginger drink brands on the market. The types of data used in the research are primary data and secondary data. The analysis method is carried out in accordance with the provisions of PPOMN in 2006. Ginger drink can also be used as an immune-boosting beverage, as demonstrated in virtual training sessions on making homemade ginger drinks to educate people about the importance of maintaining a healthy immune system. Ginger drink has the potential to reduce the risk of diseases like type 2 diabetes, as it contains gingerol and shogaol, which can inhibit fat synthesis and improve insulin sensitivity. The utilization of ginger in the production of instant powdered ginger drinks and ginger milk drinks in micro and small businesses (UMKM) has also been carried out. This production involves cooking, filtering out ginger residue, adding palm sugar and granulated sugar, and packaging.